A Scalable Unsegmented Multiport Memory for FPGA-Based Systems. (31st December 2015) - Townsend, Kevin R.; Attia, Osama G.; Jones, Phillip H.; Zambreno, Joseph
Abstract : On-chip multiport memory cores are crucial primitives for many modern high-performance reconfigurable architectures and multicore systems. Previous approaches for scaling memory cores come at the cost of operating frequency, communication overhead, and logic resources without increasing the storage capacity of the memory. In this paper, we present two approaches for designing multiport memory cores that are suitable for reconfigurable accelerators with substantial on-chip memory or complex communication. Our design approaches tackle these challenges by banking RAM blocks and utilizing interconnect networks which allows scaling without sacrificing logic resources. With banking, memory congestion is unavoidable and we evaluate our multiport memory cores under different memory access patterns to gain insights about different design trade-offs. We demonstrate our implementation with up to 256 memory ports using a Xilinx Virtex-7 FPGA. Our experimental results report high throughput memories with resource usage that scales with the number of ports.